Comparison of plate, calcanealplasty and external fixation in the management of calcaneal fractures. (October 2019) - Vicenti, Giovanni; Carrozzo, Massimiliano; Solarino, Giuseppe; Caizzi, Gianni; De Crescenzo, Angelo; Portaluri, Mauro; Mori, Claudio Maria; Vittore, Donato; Moretti, Biagio
Highlights: The paper is very interesting because is focus on a hot topic, the calcaneal fractures and the different types of treatment. We hope that the publication is suitable for your important journal. In literature few articles comapre 3 different treatment for calcaneal fracture. Abstract: Objective: Managing displaced intra-articular calcaneal fractures remains controversial. The purpose of this study is to compare and identify the surgical technique with the best outcomes for the treatment of intra-articular calcaneal fractures. Materials and methods: This is a retrospective multicentric study conducted between February 2000 and June 2014 in 206 patients with intra-articular calcaneal fractures presenting to the outpatient or emergency department of three different orthopaedic departments. The patients were treated with one of the following techniques: 1. Open reduction and internal fixation with screws and plate; 2. Percutaneous reduction and monolateral external fixation; and 3. Balloon-assisted reduction, pin fixation and tricalcium phosphate augmentation. Results: Patients treated with open reduction and internal fixation using an extensive lateral approach had a mean AOFAS score of 71 points; those treated through a minimal incision and reduction and fixation with an external fixator had a mean score of 83.1 points; and those treated with the balloon-assisted reduction, pin fixation and tricalcium phosphate augmentation had a mean score of 78.75 points. No statistically difference was found comparing the three types of treatment. Conclusion: Displaced intra-articular calcaneal fractures are still technically demanding injuries to manage. The results of this study suggest that in comparison to open reduction, a percutaneous reduction and fixation leads to higher but not statistical functional scores minimizing the wound-healing complications.